Econometric Insights into South Asia’s Monetary, Output, and Price Dynamics: A Simultaneous Equation Modeling Approach - Awan, Asma; Nawaz, Farhan Zaib; Bashir, Furrukh; Khan, Anam (Pakistan Journal of Humanities and Social Sciences, 2023)
This study focuses on investigating the simultaneous relationship among money supply, inflation, and output of emerging South Asian countries. Data from seven countries in the South Asian region, spanning from 2000 to 2022, is collected for the analysis. Three variables are considered endogenous: Money Supply, Output, and Inflation. Following the fulfillment of assumptions, we employed the Panel Two-Stage Least Squares (Panel 2SLS) method to examine the relationship between money, output, and prices. The results indicated a significant bidirectional relationship between output and money supply, meaning that a higher money supply is associated with increased output and vice versa. Additionally, a unidirectional empirical relationship is observed between inflation and money supply. As the money supply does impact the output, so neutrality of money does not hold. The study recommends South Asian countries establish a policy framework that cautiously adjusts the money supply, balancing the need to prevent excessive inflation or deflation to maintain sufficient liquidity to support optimal economic output.